Determination of Chemical Irritation Potential Using a Defined Gene Signature Set on Tissue-Engineered Human Skin Equivalents - Amy L. Harding; Craig Murdoch; Simon Danby; Md Zobaer Hasan; Hirofumi Nakanishi; Tetsuo Furuno; Sirwan Hadad; Robert Turner; Helen E. Colley (JID Innovations, 2021)
There are no physical or visual manifestations that define skin sensitivity or irritation; a subjective diagnosis is made on the basis of the evaluation of clinical presentations, including burning, prickling, erythema, and itching. Adverse skin reaction in response to topically applied products is common and can limit the use of dermatological or cosmetic products. The purpose of this study was to evaluate the use of human skin equivalents based on immortalized skin keratinocytes and evaluate the potential of a 22-gene panel in combination with multivariate analysis to discriminate between chemicals known to act as irritants and those that do not. Test compounds were applied topically to full-thickness human skin equivalent or human ex vivo skin and gene signatures determined for known irritants and nonirritants. Principle component analysis showed the discriminatory potential of the 22-gene panel. Linear discrimination analysis, performed to further refine the gene set for a more high-throughput analysis, identified a putative seven-gene panel (IL-6, PTGS2, ATF3, TRPV3, MAP3K8, HMGB2, and matrix metalloproteinase gene MMP-3) that could distinguish potential irritants from nonirritants. These data offer promise as an in vitro prediction tool, although analysis of a large chemical test set is required to further evaluate the system.